Pengaruh Penyediaan Modul Keperawatan Halusinasi Terhadap Kemampuan Keluarga Dalam Merawat Anggota Keluarganya Yang Mengalami Halusinasi Tahun 2013 - Nilai Utami Nurhasanah; Ira Kusumawaty; Sari Wahyuni (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2014)
Hallucinations can interfere perception of the five senses which include hallucinations of hear, see, smell, touch and taste, not only pose a nuisance to the patient concerned, however, resulted in doubled burden for the family. The diversity of behaviors that appear when clients back home for family raises its own stressors. Families are required to be able to care for family members who experienced hallucinations as a sub system so that clients can live independently family to live a life and not be a burden to the family . Hallucinations nursing module can be one of the tools to enhance the ability of families to care for family members who experience hallucinations. The purpose of this study was to determine the effect of the provision of nursing module hallucinations on the ability of families to care for family members who experience hallucinations. This research applied quantitative research methods, "pre-test and post-test one group design". The research was conducted on the family members of his family suffered hallucinations and outpatients of Mental Hospital Ernaldi Bahar Palembang by purposive sampling technique. Form of intervention is to provide and explain the nursing module hallucinations, which includes aspects of psychopharmacology, psychotherapy, psychosocial and psikoreligius. Based on the Wilcoxon test with p value 0.05 was obtained research results thatthere is a significant difference in the ability of the family in caring for family members who experienced hallucinations between after the explanation and before explanation of nursing module hallucinations, in other words there is significant influence of the provision of nursingmodule hallucinations on the ability of families to care for family members experiencing hallucinations with p value 0.013. This research provides important facts family's ability to care hallucinations for the patient so that the patient can undergo hallucinations later life.